Wanprestasi dalam Pelaksanaan Perjanjian Pinjam Meminjam Pada Lembaga Keuangan Mikro Syariah Karawang - Aam Hernita Sriwulan; Puti Priyana (Wajah Hukum, 2021)
The implementation of lending and borrowing money at the Karawang Islamic Microfinance Institution (LKMS) is based on an agreement between the two parties with the aim of providing capital for business development. However, in the implementation of these loans, problems are still encountered in the form of broken promises or defaults made by the debtor customer. The purpose of this research is to find out how the implementation of the loan and loan agreement at the Islamic Microfinance Institution (LKMS) X in Karawang, what are the forms and factors that cause defaults to occur at the X Sharia Microfinance Institution (LKMS) in Karawang, and how the efforts to resolve default carried out by the X Financial Institution (LKMS) in Karawang. This study uses a normative juridical method. Based on the results of research on the implementation of the lending and borrowing agreement at the Sharia Microfinance Institution (LKMS) X in Karawang, it is bound by a written agreement, the form of default that occurs is in the form of not performing achievements, performing achievements but partly, implementing achievements but too late. Factors occur in default, uncertainty in decision making, lack of coordination, misuse of loan funds, and business not running smoothly. Efforts to solve it include intensive collection, issuance of warning letters, customer summons, extension of loan terms and collateral seizure.